2020
DOI: 10.1097/brs.0000000000003718
|View full text |Cite
|
Sign up to set email alerts
|

Sports-related Cervical Spine Fracture and Spinal Cord Injury

Abstract: Study Design. Retrospective cohort study. Objective. Assess trends in sports-related cervical spine trauma using a pediatric inpatient database. Summary of Background Data. Injuries sustained from sports participation may include cervical spine trauma such as fractures and spinal cord injury (SCI). Large database studies analyzing sports-related cervical trauma in the pediatric population are currently lacki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 27 publications
3
27
0
Order By: Relevance
“…The results in the current study present sport incidents as the most frequent injury mechanism leading to cervical spine fractures (40% of all cervical patients; mean age 14.6 ± 3.8 years). High-schoolers (6) and adolescents (5), out of a total of 12 patients (91.7%), accounted for the majority of these patients, which is comparable to reports in the literature; the incidence of cervical spine injuries in sports increases with age [ 24 ]. Furthermore, the current data reveal that road incidents have decreased over the years: from 2002 to 2007, 16/44 (36.4%) patients suffered spinal fractures in a road incident, whereas from 2014 to 2019, the number decreased to 7/56 (12.5%) patients, which is in contrast to the extant literature [ 12 , 20 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 72%
“…The results in the current study present sport incidents as the most frequent injury mechanism leading to cervical spine fractures (40% of all cervical patients; mean age 14.6 ± 3.8 years). High-schoolers (6) and adolescents (5), out of a total of 12 patients (91.7%), accounted for the majority of these patients, which is comparable to reports in the literature; the incidence of cervical spine injuries in sports increases with age [ 24 ]. Furthermore, the current data reveal that road incidents have decreased over the years: from 2002 to 2007, 16/44 (36.4%) patients suffered spinal fractures in a road incident, whereas from 2014 to 2019, the number decreased to 7/56 (12.5%) patients, which is in contrast to the extant literature [ 12 , 20 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 72%
“…Short-track speed skating (STSS) is an extreme sport in pursuit of extreme speed and explosive force. In such a sport, once falling or wrestling due to improper operation, athletes are prone to serious injuries under the inertia of high-velocity movement, among which cervical spine injury (CSI) is a common one [ 2 , 3 ]. According to relevant data, the risk of serious CSI in STSS is as high as 10%-20% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“… 11 Another study called for more attentions on pediatric cervical SCI, because up to 80% of spine injuries occur in the cervical region in children compared with 30% in adult. 12 The cervical SCI in children and adolescents can be directly caused by contact sports. Among 468 sports-related cervical fractures, 103 patients had cervical cord injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Among 468 sports-related cervical fractures, 103 patients had cervical cord injuries. 12 High cervical injury incidences in children may be probably caused by the greater head to body ratio and relatively underdeveloped paraspinal musculature. 12 , 13 Surprisingly, it has been also reported that 1 in 60,000 newborns are complicated by SCI as a consequence of prolonged delivery and abnormal position of the neonate during delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation